SELF-CONFIDENCE IN HENRY FIELDING’S NOVEL TOM JONES - Sunardi Sunardi; Darman Sitepu; Zulfan Sahri (Universitas Islam Sumatera Utara (UISU), 2017)
Abstract Self-confidence is the core point of this research. Self confidence is a feeling that makes people think that they will do better after their efforts, a feeling that they can know more over time, a feeling that they can change themselves to adapt to the environment.There are three points of discussion under the topic. The first is self-confidence in facing family problem. There is no family without a problem and every single problem could be settled by means of self-confidence. This is followed by self-confidence in love as the second point. Love is a universal nuance that comes to everybody’s uplifting or crushing the person concerned and again by self-confidence love becomes a ladder to betterment in life. The third is self confidence in self-identity. A man will never be considered a man unless he has self-identity, which may appear in various forms, one of which is social standing. The main theory of self-confidence in taken from Brown stating that confidence is the belief that one will perform in a correct proper effective way. This research is conducted with descriptive qualitative method proposed by Krathwohl (1998), exploring social issues to be an epitome of guidelines. The results show that the protagonist has a strong self-confidence in facing family problem, love and self-identity. He faces a lot of problems in his family and this happens because he is an adopted child. However, through his strong self-confidence he could settle all the obstacles nicely and finally his self-confidence gives comfort to him. Key words: confidence, family, love, identity.